1997
DOI: 10.2214/ajr.169.6.9393170
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral tubular obstruction: an unusual complication of urographic contrast media.

Abstract: An unusual complication of urography with a characteristic radiologic appearance is presented. This complication was transient and reversible in our patients. Unilateral tubular blockage induced by a contrast agent must be considered when the contralateral kidney shows evidence of ureteral obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Segmental, wedge-shaped nephrograms on delayed imaging studies have only rarely been reported. Anecdotal case reports were described by Ishikawa et al in 1985 [ 4 , 5 ], by Pazmino et al in 1983 [ 6 ], by Braedel et al in 1987 [ 23 ], and by Trueba-Arguinarena et al in 1997 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Segmental, wedge-shaped nephrograms on delayed imaging studies have only rarely been reported. Anecdotal case reports were described by Ishikawa et al in 1985 [ 4 , 5 ], by Pazmino et al in 1983 [ 6 ], by Braedel et al in 1987 [ 23 ], and by Trueba-Arguinarena et al in 1997 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal case reports were described by Ishikawa et al [17] in 1985, by Pazimiño et al [18] in 1983, by Braedel et al [19] in 1987, and by Trueba-Arguinareña et al [20] in 1977. Yamazaki et al [21] reported focal residual contrast media in 16% (17/105) of patients by delayed CT at 24 h following abdominal angiography and found no association with CIN.…”
Section: Discussionmentioning
confidence: 99%